University funding mechanicsm - Ahmed, A. (2000)
The greatest asset currency in the New Economy will be a well-trained and educated population with tertiary education playing a vital role in the intellectual advancement and fulfillment of individuals and in the development of a creative, socially cohesive community and in the pursuit of life long learning. Universities in particular educate future leaders and develop the high level technical capabilities that underpin economic growth. However, the cost of running (public sector burden) Universities in particular keeps increasing, leading to national policies on education with trade-offs between primary, secondary and tertiary education due to limited resources. In Malaysia, we are, as I understand very interested in reengineering the way we fund our universities to make universities more cost-effective,transparent and accountable. It is with this view that I am going to approach my discussion.